2020
DOI: 10.1186/s12876-020-01516-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resistant starches on inflammatory bowel disease in preclinical and clinical settings: a systematic review and meta-analysis

Abstract: Background Inflammatory bowel disease (IBD) is a debilitating chronic disease with limited treatment options. Resistant starches may represent a novel treatment for IBD. However, its efficacy and safety remain unclear. Our objective was to perform a systematic review to summarize the preclinical and clinical effects of resistant starch, which may help guide future studies. Methods Medline, EMBASE, and the Cochrane Central Register we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“…Standard deviations are listed in Table S1 . Starch degradation and amino acid metabolism are associated with gastrointestinal disorders such as IBD [ 28 ], while heme biosynthesis has been shown to contribute to bacterial virulence, promote inflammation, and worsen the prognosis of patients with IBD [ 29 ]. With respect to the effect of lactulose ( Figure 7 ), heme biosynthesis ( Figure 7 , Nos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard deviations are listed in Table S1 . Starch degradation and amino acid metabolism are associated with gastrointestinal disorders such as IBD [ 28 ], while heme biosynthesis has been shown to contribute to bacterial virulence, promote inflammation, and worsen the prognosis of patients with IBD [ 29 ]. With respect to the effect of lactulose ( Figure 7 ), heme biosynthesis ( Figure 7 , Nos.…”
Section: Resultsmentioning
confidence: 99%
“…In IBD patients, starch degradation and amino acid metabolism pathway were significantly affected. Therefore, dietary fibers, such as resistant starches, are proposed as a promising treatment for IBD [ 28 ]. The present study revealed similar changes in the starch degradation and amino acid metabolism pathway in AOM/DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs), especially butyrate, contribute to the well-being of colonocytes with a possible role in the prevention of colon cancer [ 69 , 70 , 71 ]. In addition, increases in SCFAs result in lowering of the bowel pH, and this contributes to hindering the proliferation of pathogenic bacteria and reducing inflammation in irritable bowel disease [ 72 ]. In addition, the foods with high resistant starch have low glycaemic index and can help in preventing the onset of type II diabetes and obesity [ 69 , 73 ].…”
Section: Manipulation Of Starch Compositionmentioning
confidence: 99%
“…One of the few human studies indicates that RS contributes to the maintenance of clinical remission in patients with IBD and reduces the intensity of symptoms associated with active disease. It is also associated with an increase in SCFA production [ 102 ]. In another study, Rose et al presented that starch-entrapped microspheres, due to their maintenance of low pH and their involvement in butyrate production, can reduce harmful bacteria, for example Bacteroides and Fusobacterium [ 103 ].…”
Section: Link Between Dietary Fiber and Ibdmentioning
confidence: 99%